Sosialisasi Pengelolaan Sampah Sebagai Bahan Bakar untuk Pembangkit Listrik Tenaga Sampah (PLTSa) dengan Sistem Strategic Partner - A. Besse Riyani Indah; S Bahri; Mulyadi -; R Hanafi; S Asmal; F Mardin; M Rusman; I Bakri; Nilda -; D R Mudiastuti; S Mangenre; I Setiawan; M A Darmawan; K Amar; N I Syamsul (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2020)
Population density is one of the triggers for the increasing volume of waste including plastic waste. Waste is one problem that needs attention, especially in urban areas. Waste can be used as a source of renewable energy which is very abundant but the obstacle is that until now it has not been optimally utilized. However, at present, this pattern of thinking has begun to be pushed aside after the implementation of PLTSa in the garbage disposal area and will increase public awareness of the environment. There are several management methods that can be used to make waste as fuel to generate electricity, namely, the thermal conversion process and the biological conversion process. The process of managing waste as fuel will be even better if it is carried out using a strategic partner method. The Environmental Agency of Pangkep Region has implemented a waste bank program so that waste can be well coordinated in several districts. The problem faced by the waste bank in Pangkep region is the behavior of sorting waste which is still difficult, the results of sorting waste have not been fully utilized, and there is no understanding regarding waste management using the PLTSa mechanism. To increase the knowledge of the waste bank regarding the utilization of waste with the PLTSa mechanism, socialization is carried out with the output of the waste bank manager to find out the potential for waste to become PLTSa fuel, the waste bank manager can find out the mechanism of partner cooperation in realizing PLTSa, and guidelines for designing waste as fuel. PLTSa. This activity was carried out at the Environmental Agency of Pangkep Region with participants representing several waste banks in Pangkep Region.